Pomological, organoleptic, and biochemical values of Norwegian heritage apple cultivars - Mekjell Meland; Oddmund Frøynes; Darius Kviklys; Dragana Dabić Zagorac; Milica Fotirić Akšić (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science)
Almost 10,000 of apple cultivars are described worldwide but only a few of them are dominating in commercial apple orchards. The decline in genetic diversity could lead to negative consequences in terms of adaptability, resistance and even consumption. Apple genetic resources in Norway are conserved in several local clonal archives. The aim of this study was to evaluate Norwegian heritage apple cultivars from a pomological, agronomical, and chemical point of view, identify the most important quality parameters, and select cultivars with desirable traits for modern markets and breeding purposes. In total 75 heritage and 4 standard apple cultivars were evaluated at the Norwegian Institute of Bioeconomy Research – NIBIO Ullensvang, during 2018–2020. Based on individual investigations of various fruit quality characters, cultivar groups with special properties were selected for the industry, for making concentrate and fresh juice, and for medical properties. According to the soluble solid content, sweetness index, fruit size, acid, dry matter, and phenolic content, several groups of cultivars have high potential value for modern breeding programmes. Based on overall fruit quality, heritage cultivars Løeeple, Raud Gravenstein, and Rondestveit were selected for fresh consumption.